Pancreatic Cancer Malnutrition and Pancreatic Exocrine Insufficiency in the Course of Chemotherapy in Unresectable Pancreatic Cancer - Kiriukova, Mariia; de la Iglesia Garcia, Daniel; Panic, Nikola; Bozhychko, Maryana; Avci, Bartu; Maisonneuve, Patrick; de-Madaria, Enrique; Capurso, Gabriele; Sandru, Vasile (Frontiers in Medicine, 2020)
BACKGROUND: Malnutrition and cachexia are common in patients with advanced pancreatic ductal adenocarcinoma (PDAC) and have a significant influence on the tolerance and response to treatments. If timely identified, malnourished PDAC patients could be treated to increase their capacity to complete the planned treatments and therefore, possibly, improve their efficacy. AIMS: The aim of this study is to assess the impact of nutritional status, pancreatic exocrine insufficiency (PEI), and other clinical factors on patient outcomes in patients with advanced PDAC. METHODS: PAncreatic Cancer MAlnutrition and Pancreatic Exocrine INsufficiency in the Course of Chemotherapy in Unresectable Pancreatic Cancer (PAC-MAIN) is an international multicenter prospective observational cohort study. The nutritional status will be determined by means of Mini-Nutritional Assessment score and laboratory blood tests. PEI will be defined by reduced fecal elastase levels. Main outcome: adherence to planned chemotherapy in the first 12 weeks following the diagnosis, according to patients’ baseline nutritional status and quantified and reported as ‘percent of standard chemotherapy dose delivered.’ Secondary outcomes: rate of chemotherapy-related toxicity, progression-free survival, survival at 6 months, overall survival, quality of life and the number of hospitalizations. Analysis: chemotherapy dosing over the first 12 weeks of therapy (i.e. percent of chemotherapy received in the first 12 weeks, as defined above) will be compared between well- and malnourished patients. Sample size: based on an expected percentage of chemotherapy delivered of 70% in well-nourished patients, with a type I error of 0.05 and a type II error of 0.20, a sample size of 93 patients per group will be required in case of a percentage difference of chemotherapy delivered of 20% between well-nourished and malnourished patients, 163 patients per group in case of a difference of 15% between the groups and 356 patients per group in case of a 10% difference. Centers from Russia, Romania, Turkey, Spain, Serbia, and Italy will participate in the study upon Local Ethics Committee approval. DISCUSSION: PAC-MAIN will provide insights on the role of malnutrition and PEI in the outcomes of PDAC. The study protocol was registered at clinicaltrials.gov as NCT04112836.